Growth effects of spatial redistribution policies - Calin Arcalean; Gerhard Glomm; Ioana Cosmina Schiopu (Center for Economic Studies and ifo Institute (CESifo), 2012)
Regional income disparities have increased in many European countries recently, even as national and supra-national policy instruments were created to correct them. To explain these evolutions, we develop a two-region, two-sector model with migration and public investment in infrastructure and education. Accumulation and creation of new ideas and technologies as well as migration are at the core of differential regional growth. In this framework, we assess the effectiveness of structural funds, modelled on the EU policy. In a numerical example calibrated to Portugal, we find that, to diminish the initial gap in income per capita, the backward region needs to receive over 8% of its own GDP in structural funds, while the actual disbursements were around 4%. We also find that maximizing innovation in the backward region conflicts in the short run with the goal of maximizing its income per capita. Moreover, the rich region has an incentive to bias the allocation of structural funds towards human capital formation.
Keywords: O10; H70; R58; R12; 330; two-region economy; structural change; migration; regional policy; European Union